Gaya Komunikasi dan Kepemimpinan Kapolres Indarto dalam Meningkatkan Kinerja Polres Metro Bekasi Kota - Marlina, Marlina; Kurniaty, Lona; Tamica, Shendy (PERSPEKTIF, 2020)
Communication style and leadership of a leader is a key to improving the quality of the performance of its members to achieve success targets. Likewise with the Chief of the Indarto Resort Police, who managed to lead members of his police force until the Bekasi City Metro District Police succeeded in receiving various awards for his achievements. That's why the purpose of this research is to understand how Indarto's communication style and leadership style as the Police Chief in improving the performance of members of the Jakarta Bekasi City Police Precinct, and what things influence the implementation of Indarto's communication style as a leader. This research uses a qualitative approach, with data collection techniques through interviews, observation, and literature review. the informants in this study were selected by using purposive sampling technique. The data collected is analyzed using data triangulation techniques. The results of this study indicate that the leadership style used by the Indarto Police Chief is the Acocratic style and Democratic Style. Whereas the communication style for Indarto Police Chief is the Controlling style, Dynamic style, and Reliquishing styleÂ Â